2011
DOI: 10.1063/1.3571007
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of water entry in hydrophobic channels of carbon nanotubes

Abstract: Experiments and computer simulations demonstrate that water spontaneously fills the hydrophobic cavity of a carbon nanotube. To gain a quantitative thermodynamic understanding of this phenomenon, we use the recently developed two phase thermodynamics method to compute translational and rotational entropies of confined water molecules inside single-walled carbon nanotubes and show that the increase in energy of a water molecule inside the nanotube is compensated by the gain in its rotational entropy. The confin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
93
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 28 publications
6
93
4
Order By: Relevance
“…The 2PT method has found successful application in several related problems [38][39][40][43][44][45].…”
Section: A Translocation Of Sirna Inside Cntsmentioning
confidence: 99%
“…The 2PT method has found successful application in several related problems [38][39][40][43][44][45].…”
Section: A Translocation Of Sirna Inside Cntsmentioning
confidence: 99%
“…Despite extensive studies, there are conflicting views of whether filling is driven by the entropy or energy of transfer. 3,16,20,21 The magnitude and even the sign of the entropy of single-file water remain contentious. An early study by Vaitheeswaran et al 3 reported a near-zero entropy of transfer from bulk into a quasi-infinite nanotube obtained by periodic replication of a finite nanotube segment.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent studies, density of states formalisms were used to estimate the translational and rotational contributions to the entropy, producing positive transfer entropies for model TIP3P and SPC/E water in (6,6) carbon nanotubes. 20,21 To resolve these discrepancies in the calculated entropies of single-file water, we here use the most direct method to determine the entropy of transfer, by examining the thermodynamics of filling an open carbon nanotube in equilibrium with bulk TIP3P water in molecular dynamics (MD) simulations over a range of temperatures. We first describe the simulation setup and the analysis methods, including those for periodically replicated nanotubes (with the issue of the bulk reference discussed in the Appendix).…”
Section: Introductionmentioning
confidence: 99%
“…The 2PT method has been shown to be accurate and efficient in determining the entropy of pure liquids from classical MD simulations of bulk water in good agreement with more expensive method 5,6 and to access the thermodynamics of water under hydrophobic confinement and surfaces. 8 It has also recently been applied to understanding the thermodynamics of hydrocarbons at high temperatures and pressures and of metal alloys using BOMD simulations. 9 A closely related technique to calculate the entropy based on the partial pair correlation function has been recently devised by Chakravarty and co-workers.…”
Section: Introductionmentioning
confidence: 99%